MENINGKATKAN PENGETAHUAN HKI DAN EFISIENSI PEMBUKUAN DENGAN MICROSOFT OFFICE EXCEL UNTUK PELAKU UMKM TARAKAN - Muhammad Zidan Fariz; Awang Pradana; Jabir Anshari; Senia Rombe Pabuntang; Uways Al-Qorny (LPPM Universitas Abdurrab, 2025)
Empowerment of Micro, Small, and Medium Enterprises (MSMEs) plays a crucial role in supporting the community's economy. However, many MSME actors face challenges such as low awareness of Intellectual Property Rights (IPR) and limited use of digital technology in business operations. This community service activity aims to enhance the understanding of MSME actors in Tarakan City regarding the importance of IPR and provide basic skills in digital bookkeeping using Microsoft Excel. The implementation methods include interactive presentations and training with a case study approach. Participants were introduced to the trademark registration process through the Online Single Submission (OSS) system to obtain a Business Identification Number (NIB). Additionally, the Microsoft Excel training focused on creating simple cash tables, automated calculations, and utilizing basic features to support digital financial record-keeping. The results showed an improvement in participants' understanding of the importance of business legality and basic digital bookkeeping skills. A total of 85% of participants stated that the training was highly beneficial in increasing business management efficiency. The outputs of the activity include IPR and Microsoft Excel training modules, training documentation, and evaluation reports. This training is expected to encourage the adoption of digital technology and IPR protection to improve the competitiveness of MSMEs in Tarakan City.